Pendampingan Pasien Kanker Melalui Guided Imagery Berbasis Virtual Reality di Yayasan Kanker Indonesia: Assistance for Cancer Patients Through Guided Imagery Based on Virtual Reality at the Indonesian Cancer Foundation - Yumni, Fathiya Luthfil; Maulidiyah, Ummi Masrufah; Rosadi, Aswin; Firman, Firman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The incidence of cancer is 19.3 million new cases of cancer and almost 10 million deaths due to cancer every year. According to data from GLOBOCAN, new cases of cancer in Indonesia are 396,914 and the incidence of deaths is 234,511, which means an increase of 13.8% compared to the addition of new cases in the previous year. The prevalence of cancer pain is reported to be 51% in cancer patients based on the phase of the disease and/or the phase of treatment. This service aims to assist cancer patients through virtual reality-based guided imagery at the Indonesian Cancer Foundation. Methods for implementing activities, in the form of lectures, discussions, and practice. The training which was carried out for 1 day was effective in increasing knowledge and effectively reducing complaints of pain and anxiety, as evidenced by significant changes in the level of knowledge of dealing with pain, the results of the pretest knowledge were high at 20%, then after the post-test knowledge increased to 93.33%. Meanwhile, the pre-test results reduced anxiety symptoms by 6.67%, and after the post-test, patients' lack of anxiety increased significantly to 60%. Thus, it is hoped that with the knowledge and level of anxiety that participants have, they can reduce pain complaints and reduce anxiety symptoms in cancer patients at the Indonesian Cancer Foundation.